EFEKTIVITAS PENGGUNAAN VIDEO ANIMASI: STUDI EKSPERIMEN PADA PEMBELAJARAN FIQIH DI MTS ASH SHABIRIN SAMARINDA - Fahmi, Muhammad; Hajriana, Hajriana; Rahman, Fathur (STIT Ibnu Rusyd Tanah Grogot, 2024)
This study is motivated by the low learning outcomes of students at MTs Ash Shabirin Samarinda. The aim of this study is to determine whether the use of animated videos is effective in improving the learning outcomes of eighth-grade students in the subject of Fiqh at MTs Ash Shabirin Samarinda. This research is an experimental study with a quantitative approach. The population used in this study consists of all eighth-grade students at MTs Ash Shabirin Samarinda. The research design used is the pretest-posttest control group design, which aims to determine whether there is a significant difference between the experimental class and the control class. Data collection techniques used include observation, tests, and documentation. Data analysis techniques used non-parametric tests due to the non-normal distribution of data, namely the Wilcoxon test, and the hypothesis test used the Mann-Whitney test. The validity and reliability of the data were tested using IBM SPSS version 24 for Windows. The results of the study show that the average Fiqh learning outcomes using animated videos are higher than the average Fiqh learning outcomes without using animated videos. The results of the Mann-Whitney hypothesis test show an Asymp. Sig. (2-tailed) value of 0.040 < 0.05, which means the hypothesis is accepted. Therefore, it can be concluded that the use of animated videos is effective in improving students' learning outcomes at MTs Ash Shabirin Samarinda.